1987
DOI: 10.1002/polb.1987.090250301
|View full text |Cite
|
Sign up to set email alerts
|

Influence of structural and morphological factors on the mechanical properties of the polyethylenes

Abstract: SynopsisForce-length relations at ambient temperature have been determined for a set of polyethylenes Hwhich represent a wide range in molecular weight and molecular constitution. Taking advantage of previous work from this laboratory, samples have been prepared in such a manner that the important independent structural variables can be identified and isolated and their influence on the different aspects of the deformation process assessed. Partial melting-recrystallization processes appear to play an importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
238
0
1

Year Published

1988
1988
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 347 publications
(263 citation statements)
references
References 108 publications
24
238
0
1
Order By: Relevance
“…melt-spinning or fibres prepared from semi-dilute polymer solutions) and the process variables, as extensively described in the literature [27,29,[30][31][32][33][34][35]. During cold-drawing the lamellar structures are transformed into fibrillar structures by rotation/translation of (parts of) lamellae and/or by local melting of the lamellae due to local high stress concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…melt-spinning or fibres prepared from semi-dilute polymer solutions) and the process variables, as extensively described in the literature [27,29,[30][31][32][33][34][35]. During cold-drawing the lamellar structures are transformed into fibrillar structures by rotation/translation of (parts of) lamellae and/or by local melting of the lamellae due to local high stress concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…The observed differences were attributed to level of crystallinity. 20 The effect of cooling rate was only observed indirectly in ref 19 since they used tensile experiments, where brittle failure was observed for the lower molecular weight, slowly cooled samples. In macroscopic tensile behavior localization and failure phenomena cannot be overcome as in the compressive measurements of this study.…”
Section: Strain Hardening Petmentioning
confidence: 99%
“…A similar decrease of τ was observed in simulations of n-alkanes 43 and experimentally it has been found that ultimate tensile strength of certain polymeric systems, such as amorphous polyethylene, decreases with increasing molecular weight. 63 Such a decrease in τ is non-trivial, since one expects longer chains to exhibit more chain "entanglement". Such a view neglects the importance of packing, however, which is crucially important in the low temperature glass regime.…”
Section: Calculation Of τmentioning
confidence: 99%